2021
DOI: 10.1021/acscatal.1c04022
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Stable Co/β-Mo2C Catalyst for Hydroformylation

Abstract: The hydroformylation of olefins is one of the most important industrial processes used for aldehyde synthesis, which commonly involves the use of scarce and expensive rhodium-based catalysts. It is therefore important to develop inexpensive catalysts, e.g., cobalt-based catalysts with sufficiently high activity and stability for hydroformylation. However, conventional metallic Co clusters, acting as active centers, suffer from low activity and severe metal leaching. Here, we show that Mo 6 C 2 -bonded Co can s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…4,5 Another typical hydroformylation catalyst system has been cobalt complexes, such as CO-protected cationic cobalt catalysts, for which researchers have faced a long-standing challenge to stabilize the cobalt catalysts with respect to decomposition to inactive cobalt metal. 6,7 Take, as an example of heterogeneous reactions, the dry reforming of methane and carbon dioxide to produce CO and H 2 . 8−10 Nickel catalysts currently can give rise to ∼100% methane conversion with 0.9 of H 2 /CO ratio at 800 °C, yet the coke of catalysts has been hardly avoidable, which has led to poor long-term performance.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Another typical hydroformylation catalyst system has been cobalt complexes, such as CO-protected cationic cobalt catalysts, for which researchers have faced a long-standing challenge to stabilize the cobalt catalysts with respect to decomposition to inactive cobalt metal. 6,7 Take, as an example of heterogeneous reactions, the dry reforming of methane and carbon dioxide to produce CO and H 2 . 8−10 Nickel catalysts currently can give rise to ∼100% methane conversion with 0.9 of H 2 /CO ratio at 800 °C, yet the coke of catalysts has been hardly avoidable, which has led to poor long-term performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, catalytic activity and stability of a catalyst are often an impossible combination at the same time for some chemical processes. The prime example of homogeneous reactions is the hydroformylation of alkenes with carbon monoxide and hydrogen to produce aldehydes. Although HRh­(CO) 4 was well known as a highly active hydroformylation catalyst, it required high-cost excess ligands to inhibit the catalyst decomposition to undesired Rh–carbonyl species. , Another typical hydroformylation catalyst system has been cobalt complexes, such as CO-protected cationic cobalt catalysts, for which researchers have faced a long-standing challenge to stabilize the cobalt catalysts with respect to decomposition to inactive cobalt metal. , Take, as an example of heterogeneous reactions, the dry reforming of methane and carbon dioxide to produce CO and H 2 . Nickel catalysts currently can give rise to ∼100% methane conversion with 0.9 of H 2 /CO ratio at 800 °C, yet the coke of catalysts has been hardly avoidable, which has led to poor long-term performance . To reach the industry standard, a high activity and high stability of the catalysts must be satisfied at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Recently, a new class of twodimensional (2D) transition metal (TM) carbides, nitrides and carbonitrides (collectively known as MXenes) have remarkable potential applications in numerous electrochemical processes. [9][10][11][12][13][14][15][16] The special metallic electronic structure will give rise to effective electron transport, and the abundant TM atoms with empty d-orbitals are benecial for the activation of gasphase molecules; thus, MXenes have attracted considerable attention in recent years. [17][18][19] Among these MXenes, metal carbides have gained signicant interest because their electronic structures near the Fermi level are similar to those of noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Therefore, the insertion of the active metal into the tungsten carbide support can obviously adjust the electrical properties of the metal to improve the catalyst performance. Wei et al 35 found that the Co/β-Mo 2 C catalyst showed good activity and stability in hydroformylation reaction. Lewandowski et al 36 found that the catalyst obtained by uniformly dispersing Pt on Mo 2 C has high activity for hydro-denitrification and hydrodesulfurization.…”
Section: Introductionmentioning
confidence: 99%